1992
DOI: 10.1007/bf00180865
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in regional cerebral blood flow in patients with major depression using the 99mTc-HMPAO single photon emission tomography method

Abstract: Regional cerebral blood flow was investigated in 14 patients with major depression diagnosed according to the DSM-III-R criteria (six patients with single and eight patients with recurrent episodes) and in ten healthy volunteers. The mean ages of the patients and the controls were 33.5 +/- 2.7 and 31.6 +/- 2.6 years, respectively. The severity of the depression was assessed using the 17-item Hamilton Depression Scale (mean: 23.2 +/- 1.5). None of the patients was under medication. After administration of 500 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…Among these reports, the most consistent findings are hypoperfusion and hypometabolism in the anterior brain structures, especially in the prefrontal cortex [1][2][3][4][5][6][7][8][9][10][11] and the anterior paralimbic regions, [9][10][11][12][13] and similar findings have also been reported in late-life depression. [14][15][16][17] However, the clinical significance of these findings remains controversial.…”
Section: Introductionsupporting
confidence: 55%
“…Among these reports, the most consistent findings are hypoperfusion and hypometabolism in the anterior brain structures, especially in the prefrontal cortex [1][2][3][4][5][6][7][8][9][10][11] and the anterior paralimbic regions, [9][10][11][12][13] and similar findings have also been reported in late-life depression. [14][15][16][17] However, the clinical significance of these findings remains controversial.…”
Section: Introductionsupporting
confidence: 55%
“…This was mainly applicable to psychotic symptoms rated on the BPRS. While associations between increased severity of illness and reduced blood flow have been described previously, they have mostly involved patients with depression and ratings on the HDRS (Yazici et al 1992;Scott et al 1994;Bonne et al 1996). Then again, some SPECT studies have found that patients with psychotic symptoms show significantly decreased rCBF relative to both non-psychotic patients and healthy controls (Skaf et al2002;Gonul et al 2004;Benbarre et al 2005).…”
Section: Patterns Of Rcbf Among Patients and Controls In The Current mentioning
confidence: 93%
“…Cortex limits in selected cross-sections were determined through semi-automatic program, and the enumerations in the region of interest (ROI) were recorded as average enumeration. 6 pieces of ROI were placed in both sections [24] (Figure 2). Statistical analysis The data were analyzed using the Statistical Package for the Social Sciences (SPSS) for Windows, Version 18.0 software.…”
Section: Methodsmentioning
confidence: 99%